Comparing Treatment and Outcomes of Ductal Carcinoma in Situ among Women in Missouri by Race - Madubata, Chinwe C. (Breast Cancer Res Treat, 2016)
PURPOSE: To investigate whether treatment (surgery, radiation therapy, and endocrine therapy) contributes to racial disparities in outcomes of ductal carcinoma in situ (DCIS). PATIENTS AND METHODS: The analysis included 8,184 non-Hispanic White and 954 non-Hispanic Black women diagnosed with DCIS between 1996 and 2011 and identified in the Missouri Cancer Registry. Logistic regression models were used to estimate odds ratios (ORs) of treatment for race. We used Cox proportional hazards regression models to estimate hazard ratios (HRs) of ipsilateral and contralateral breast tumors for race. RESULTS: There was no significant difference between Black and White women in utilization of mastectomy (OR 1.16; 95% CI 0.99–1.35) or endocrine therapy (OR 1.19; 95% CI 0.94–1.51). Despite no significant difference in underutilization of radiation therapy (OR 1.14; 95% CI 0.92–1.42), Black women had higher odds of radiation delay, defined as at least eight weeks between surgery and radiation (OR 1.92; 95% CI 1.55–2.37). Among 9,138 patients, 184 had ipsilateral breast tumors (IBTs) and 326 had contralateral breast tumors (CBTs). Black women had a higher risk of IBTs (HR 1.69; 95% CI 1.15–2.50) and a comparable risk of CBTs (HR 1.19; 95% CI 0.84–1.68), which were independent of pathological features and treatment. CONCLUSION: Racial differences in DCIS treatment and outcomes exist in Missouri. This study could not completely explain the higher risk of IBTs in Black women. Future studies should identify differences in timely initiation and completion of treatment, which may contribute to the racial difference in IBTs after DCIS.